Comparing Iraqi Regional Differences on Infant Feeding through Breastfeeding and Formula - Grace Tribble, Anna (Kurdistan Journal of Applied Research, 2018)
Research tends to focus on the health implications of breastfeeding, but understanding associations that might drive maternal choice in infant feeding practice is also very important. To understand the relationship between women’s feeding strategies for their children and the context in which they live in Iraq, mixed methods are deployed through analysis of surveys and interviews. Using data from the 2000 and 2011 Multiple Indicator Cluster Survey, trends are quantitatively examined in breastfeeding and infant formula use for Iraq using linear probability models. Interviews are qualitatively analyzed that were collected from women in Sulaimani governorate in the Kurdish region of Iraq to begin understanding the reasons why Iraqi women initiate breastfeeding and formula use. Being urban, wealthier, and more educated increases the probability of a mother using infant formula, while only increasing wealth and increasing education are associated with increasing the probability of breastfeeding. In 2000, governorates significantly differ in the probability of mothers using infant formula (e.g. Karbala = 24.32 percentage points lower probability of using infant formula relative to Sulaimani, (p<0.0001), but differences in breastfeeding seem to be between the southern and northern governorates (e.g. Karbala = 6.78 percentage points higher probability of breastfeeding relative to Sulaimani, (p<0.01). Over the ensuing decade, the probability of breastfeeding decreases, and the probability of infant formula use increases across most governorates. Interviews provide narratives that help explain these trends such as mothers continuing to breastfeed during stressful times but using infant formula when working outside of the home. Between governorate differences could be driven by differences in conflict over the decade. This study contributes to a more nuanced perspective on infant feeding practices in Iraq at the governorate level, suggesting that future maternal-child nutrition studies need to account for the effects of where a mother lives within Iraq.